REVITALISASI LAGU SLAWA MUSIK TRADISIONAL SUKU TEHIT DI TEMINABUAN SORONG SELATAN PAPUA BARAT DAYA - sagisolo, ais (Jurnal Industri Kreatif dan Inovatif, 2025)
Revitalization of the Slawa Song: Traditional Music of the Tehit Tribe in Teminabuan, South Sorong, Southwest Papua as an Effort to Preserve Cultural Identity Amidst Modernization. The revitalization of the Slawa song, a traditional musical form of the Tehit tribe in Teminabuan, South Sorong, Southwest Papua, is an important initiative aimed at safeguarding cultural identity in the face of modernization that threatens the existence of traditional values. The central issue addressed is the gradual erosion of the traditional music identity of the Tehit tribe due to external cultural influences, raising concerns that it may disappear from the daily life of the community. The main objective is to provide space for the younger generation of the Tehit tribe to recognize and appreciate their ancestral traditions, fostering awareness of their identity as members of the Tehit tribe and protecting the continuity of their cultural heritage. Through this research, the revitalization process aims to create and design traditional musical instruments that can accompany the Slawa song possessed by the Tehit community, by incorporating several characteristic Tehit instruments. This allows for the Slawa song and its deep meanings to be revived and reintroduced. The research utilizes a qualitative methodology with an ethnomusicological approach, involving online observations and in-depth interviews to gain comprehensive insights into traditional Tehit music and efforts toward its preservation. The design of traditional Tehit music will later be presented through an audio spectrum accompanied by a visualizer featuring authentic Tehit tribal motifs.The outcomes of this research are expected to contribute to the advancement of local cultural identity and motivate the younger generation to preserve the traditional musical heritage of the Tehit tribe.